Enhancing Lecturer Quality through HRD Strategies and Support - Yanto Niode, Idris; Tantawi, Rezkiawan; Gani, Sri Yeyen (Jurnal Manajemen, 2025)
This study analyzes the impact of human resource development (HRD) strategies based on education and training on lecturer quality in higher education institutions in Gorontalo, with organizational support as a mediating variable. Using a quantitative approach and correlational method, data were collected from 84 respondents through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that both education- and training-based HRD strategies have a significant positive effect on organizational support. However, their direct effects on lecturer quality are not significant. Organizational support has a significant positive effect on lecturer quality and significantly mediates the relationship between HRD strategies and lecturer quality. These findings highlight the crucial role of organizational support in enhancing the effectiveness of HRD strategies in improving lecturer quality in higher education institutions.